Solve for "x".... -5x - 7 = - 3(x - 1)
First: eliminate parenthesis --- distribute the outer term with the terms in parenthesis.....
- 5x - 7 = - 3(x) - 3(- 1)
- 5x - 7 = - 3x - (-3)
- 5x - 7 = - 3x + 3
Sec: combine "like" terms --- combine the coefficients with the x-variable > add "3x" with both sides (when you move a term to the opposite side, always use the opposite sign).....
- 5x + 3x - 7 = - 3x + 3x + 3
- 5x + 3x - 7 = 3
- 2x - 7 = 3
Third: add 7 with both sides....
- 2x - 7 + 7 = 3 + 7
- 2x = 3 + 7
- 2x = 10
Fourth: isolate "x" on one side --- divide both terms by "-2"....
- 2x/-2 = 10/-2
x = -10/2
x = -5
2007-02-10 16:59:05
·
answer #1
·
answered by ♪♥Annie♥♪ 6
·
0⤊
1⤋
-5x-7=-3(x-1)
Grouping terms
=> -5x-3x=7+3
=> -2x=10
=> x=10/-2
=> x=-5
If you plug x=-5 into the original equation you get
-5(-5)-7=-3(-5-1)
25-7=18
18=18
So we proved that the right answer is x=-5
2007-02-10 23:46:08
·
answer #2
·
answered by Pink wolf 3
·
0⤊
0⤋
-5x - 7 = -3(x-1)
-5x-7 = -3x +3
-2x = 10
x =-5
2007-02-10 23:39:43
·
answer #3
·
answered by radne0 5
·
0⤊
0⤋
God, your questions are easy as hell.
First, follow the Order of Operations. Solve parentheses.
-5x-7=-3x+3
Transpose.
-5x+3x=7+
-2x=10
And here's the answer:
x=-5
2007-02-11 00:07:44
·
answer #4
·
answered by FLY PIG FLY! 2
·
0⤊
0⤋
distribute and simplify the left side:
-5x-7=-3x+3
add 5x to both sides:
-7=2x+3
subtract three from both sides:
-10=2x
divide by 2:
-5=x
so...
x=-5
2007-02-10 23:48:32
·
answer #5
·
answered by Captain Oblivious 6
·
0⤊
0⤋
-5x-7=-3x+3
-2x=10
x=-5
2007-02-10 23:41:40
·
answer #6
·
answered by cav 5
·
0⤊
0⤋
Go with Radne. Cav forgot to plug the answer back into the equation, which would have shown that -2 is wrong.
2007-02-10 23:45:16
·
answer #7
·
answered by billy b 3
·
0⤊
0⤋
I think is 2
x=2
Am I correct???
2007-02-10 23:45:28
·
answer #8
·
answered by Yari Jahaira ♥ 3
·
0⤊
1⤋